Možne vrste cenenih motorjev s prostornino 50 kubičnih centimetrov z majhno emisijo - Kirchberger, Roland (Strojniški vestnik, 2004)
The EURO 2 emission regulation, which has been in force since June 2002, is a challenge to the industry that produces small two-wheeler two-stroke vehicles.A summary and comparison of the available technologies, concerning costs, production technologies and aspects of performance will give a survey of the state of the art and will show possible ways of coping with this challenge. It should be classified in advance if the use of an injection system is necessary in order to meet the EURO 2 exhaust-emission regulations. Production costs are of special interest when dealing with the topic two-wheeler engines. This paper describes a method for achieving the required exhaust-emission limits without having to resort to "high-tech & high-cost" technologies. Without using any additional parts, only by optimising the given engine thermodynamics and mechanics, basic research and studies of prototypes will show how to achieve significant reductions in emissions and increases in the engine power and torque output. Various vehicle tests will show the suitability for mass production, taking into account the required modifications necessary for fulfilling the EURO 2 exhaust-emission regulations.
Keywords: motorji dvotaktni; emisija majhna; stroški mali; dvotaktni motorji; izkoristek; emisija